Spatial analysis and Localization of Selected Pharmacies Distribution of Agonist Drugs for Addiction Treatment Clients in Substance Abuse centers with GIS - Morteza Heidarimozaffar; Amin Pak (Tehran University of Medical Sciences, 2021)
Field of study and Goals: The provision of medical services and the distribution of agonist drugs in substance abuse treatment centers has led to a lack of attention to patients' treatment plans and a greater focus on drug distribution. In order to separate health and pharmaceutical services that are provided for opioid addicts in drug addiction treatment centers, a study has been designed with the aim of locating the selected pharmacy for the distribution of agonist drugs in District 21 of Tehran Municipality with a spatial approach. Materials and Methods: This applied research is a descriptive-analytical method. The spatial and descriptive data were collected from the municipality organization and treatment and food and medicine departments of Iran University of Medical Sciences and Health Services and they were analyzed using ArcGIS software. Distribution of pharmacies and drug addiction treatment centers in the study area, locating the appropriate areas, and locating the selected pharmacy were studied by using the kernel density estimation functions, hierarchical analysis, and location model - allocation in two regional and district modes with maximum coverage of drug addiction treatment centers, respectively and analyzed using SPSS software and t-test.  Results: This study shows that the distribution of pharmacies and population in different regions of the study area is commensurate. Based on the results of locating using hierarchical analysis method, all pharmacies in the study area are appropriate to be the pharmacy for distributing the agonist drugs, and the results of the location model - allocation shows that the average time, and distance to access to the selected district pharmacy is 17 minutes and 5.9 km, respectively and for the regional pharmacy is 2 minutes and 0.7 km, respectively.  Conclusion: Separation of medical services and distribution of agonist drugs is essential. The findings of this study indicate that the distribution of agonist drugs through selected regional pharmacies increases access to medicine and the satisfaction of patients.